2011
DOI: 10.1152/ajpregu.00334.2010
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone reverses reproductive and metabolic disturbances in prenatally androgenized rats via regulation of ovarian signaling mechanisms and androgen synthesis

Abstract: reverses reproductive and metabolic disturbances in prenatally androgenized rats via regulation of ovarian signaling mechanisms and androgen synthesis. Am J Physiol Regul Integr Comp Physiol 300: R869 -R875, 2011. First published January 12, 2011 doi:10.1152/ajpregu.00334.2010.-This trial explores 1) prenatally androgenized (PNA) rats as a model of polycystic ovary syndrome (PCOS) and 2) reproductive and metabolic effects of cryptotanshinone in PNA ovaries. On days 16 -18 of pregnancy, 10 rats were injected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
(32 reference statements)
0
21
0
Order By: Relevance
“…Plasma T levels increased twofold in T-injected rats compared with in controls. We built a PNA rat model by injecting rats SC with 2.5 mg/day T propionate on days 16, 17, and 18 of pregnancy (based on our previous study) (20). The pregnant women with PCOS exhibited significantly higher concentrations of T, A, and DHEAS than normal pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma T levels increased twofold in T-injected rats compared with in controls. We built a PNA rat model by injecting rats SC with 2.5 mg/day T propionate on days 16, 17, and 18 of pregnancy (based on our previous study) (20). The pregnant women with PCOS exhibited significantly higher concentrations of T, A, and DHEAS than normal pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant female rats were randomized into two groups. On days 16, 17, and 18 of pregnancy, 10 females were injected SC with 2.5 mg/day T propionate (2.5 mg/mL, Shanghai GM, purchased from the Affiliated Hospital, Heilongjiang University of Chinese Medicine) according to our previous study (20). On days 16, 17, and 18 of pregnancy, 10 females were injected SC with 0.1 mL neutral tea oil daily.…”
Section: Animalsmentioning
confidence: 99%
“…Li et al [266] reported that CT (27 mg/kg of CT in Tween 80/saline, oral gavage for 14 days) decreased plasma 17α-hydroxy progesterone in male offspring with high circulatory androgen stimulated by prenatal androgenization. Similarly, Yang et al [267] reported that CT (27 mg/kg, 14 day) attenuated the increased plasma androgen level in female offspring receiving prenatal androgenization, in association with reduction of androgen synthesis enzyme CYP17. Zhao et al [268] reported that CT (600 mg/kg of CT, oral gavage for 8 weeks) reversed the increased plasma testosterone level caused by Akt2 deletion in mice, in association with decrease of CYP17.…”
Section: Anti-cancer Activities Of Tanshinonesmentioning
confidence: 95%
“…Other CHMs, such as Radix notoginseng, have been found to have similar antidiabetic effects in mouse models, improving not only glucose tolerance and insulin action in a dose-response fashion but also ameliorating obesity (13). Similarly, Salvia miltiorrhiza Bunge has been shown to significantly improve glucose tolerance in a prenatally androgenized rat model of PCOS and to favorably impact insulin signaling in treated animals (118). Berberine, a component of Rhizoma coptidis, has been shown to improve glucose uptake and insuln action in human thecal cells with dexamethasone-induced insulin resistance (125).…”
Section: Chinese Herbal Medicinementioning
confidence: 99%